Absence of cellular hypersensitivity to muscle and thymic antigens in myasthenia gravis. Issue 11 (November 1975) - Behan, W M; Behan, P O; Simpson, J A
Abstract : Humoral antibodies to skeletal muscle and its components and to thymus have been demonstrated in the sera of patients with myasthenia gravis. A role for cellular hypersensitivity to similar antigens in the pathogenesis of the disease has been suggested by some reports of the presence of cellular immunity. A detailed immunological study using muscle and thymic antigens, including those prepared from the patients' own tissues, failed to confirm these findings. It is suggested that previous reports of cellular hypersensitivity represent the demonstration of an epiphenomenon.